Functional Python programming : discover the power of functional programming, generator functions, lazy evaluation, the built-in itertools library, and monads - Lott, Steven F. (Packt Publishing, 2018)
Python is an easy-to-learn and extensible programming language that offers a number of functional programming features. This practical guide demonstrates the Python implementation of a number of functional programming techniques and design patterns. Through this book, you'll understand what functional programming is all about, its impact on ...